Hypersensitivity to ticagrelor and low response to clopidogrel: a case report - Dai, Jing (Asia Pac Allergy, 2017)
Ticagrelor is widely used to treat acute coronary syndrome. Hypersensitivity reaction of ticagrelor is rarely recognized. A low response to clopidogrel, which occurs in up to 23% of patients, is an independent risk factor for stent thrombosis. Management of patients with a low response to clopidogrel and ticagrelor hypersensitivity who are undergoing antithrombotic therapy remains to be a challenge. Herein, we report a patient with low response to clopidogrel and ticagrelor hypersensitivity, who was successfully managed using aspirin and warfarin.